Penerapan Manajemen Risiko Pelayanan Keperawatan di Poliklinik RS An-Nisa - Rika Astri Novianti; Muhammad Hadi; Naryati Naryati; Tini Suminarti (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Hospital services are services that specifically serve the needs of the community, especially in the nursing section. Nursing services are services based on the science and procedures of nursing, which consist of bio-psycho-sicio-spiritual.Risk management is a systematic process of identifying, analyzing, evaluating, controlling and supervising and communicating risks related to all activities. This study aims to analyze. Implementation of nursing service risk management at An-nisa Polyclinic Tangerang. The method used is descriptive analytic with a cross-sectional approach. The number of samples in this study was 48 people. From the multiple logistic regression test, it was found that the factors most related to the implementation of risk management were supporting factors with a p-value of 0.050 with an OR value of 7.542 and driving factors (attitude) with a p-value of 0.028 with an OR value of 5.103. The conclusion of this study is that there is a relationship between supporting variables and the implementation of risk management at the An-Nisa Hospital Polyclinic, Tangerang. Keywords: Health Belief Model, Risk Management, Nursing Services. ABSTRAK Pelayanan Rumah Sakit merupakan pelayanan yang khusus melayani kebutuhan masyarakat, terutama di bagian keperawatan. Pelayanan keperawatan merupakan pelayanan berdasarkan pada keilmuan dan tata cara keperawatan, yang terdiri dari bio-psiko-sisio-spritual. Manajemen risiko adalah  proses sistematis identifikasi, analisa, evaluasi, pengendalian dan pengawasan serta komunikasi risiko yang ada hubungannya dengan segala kegiatan. Penelitian ini bertujuan untuk menganalisis Penerapan manajemen risiko pelayanan keperawatan di Poliklinik An-nisa Tangerang.  Metode yang digunakan adalah deskriptif analitik dengan pendekatan cross sectional. Jumlah sampel penelitian ini adalah 48 orang. Dari uji regresi logistik ganda didapatkan faktor yang paling berhubungan dengan penerapan manajemen risiko adalah faktor pendukung  dengan p-value 0,050 dengan nilai OR 7,542 dan faktor pendorong (sikap) dengan p-value 0,028 dengan nilai OR 5,103. Kesimpilannya dari penelitian ini adalah terdapat hubungan  antara variabel pendukung dengan penerapan manajemen risiko di Poliklinik RS An-nisa Tangerang. Kata Kunci: Health Belief Model, Manajemen Risiko, Pelayanan Keperawatan.